2012
DOI: 10.1111/j.1743-6109.2012.02728.x
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Characteristics of Men Who Use Phosphodiesterase Type 5 Inhibitors Based on Obtaining Patterns: Data from the Nationwide Japanese Population

Abstract: Introduction Worldwide, certain subsets of men bypass healthcare provider (HCP) interactions and obtain phosphodiesterase type 5 inhibitors (PDE5i) from uncontrolled sources. Aim To stratify men who are PDE5i users based on their obtaining patterns and investigate the characteristics that differentiate these groups. Methods A Web-based observational study con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
1
15
2
Order By: Relevance
“…Further, our study revealed that there were more smokers in the users’ group than in the nonusers’ group. This is in agreement with Kimura et al () who reported that PDE5Is users were smokers more than the non‐users. Notably, our study revealed that the ex‐smokers were less likely to use PDE5Is which could be related to improved erectile function after stopping smoking.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Further, our study revealed that there were more smokers in the users’ group than in the nonusers’ group. This is in agreement with Kimura et al () who reported that PDE5Is users were smokers more than the non‐users. Notably, our study revealed that the ex‐smokers were less likely to use PDE5Is which could be related to improved erectile function after stopping smoking.…”
Section: Discussionsupporting
confidence: 93%
“…The similarity in the rates of PDE5I use in these studies may be related to the similar geographical distribution and similar cultures in Arabic countries. On the other hand, the rate of PDE5I use reported in our study was much higher than that reported by non‐Arabic countries (UK, United States, Germany, Italy and Japan) (Harte & Meston, ; Kimura et al, ; Musacchio, Hartrich, & Garofalo, ; Schnetzler, Banks, Kirby, Zou, & Symonds, ).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Many population-based studies have reported the recreational use of PDE5 inhibitors among young men aged 18 to 44 years [4,5,11,14]. Indeed, these drugs are approved for treating ED patients, but young healthy men may wish to use them to enhance their sexual performance.…”
Section: Discussionmentioning
confidence: 99%